The media morphosis of science communication during crises - Rocco Caferra; Giuseppe Di Liddo; Andrea Morone; David Stadelmann (Scientific Reports)
Abstract Effective science communication is crucial in informing citizens in times of crisis. The ICT-driven metamorphosis of the media industry (media-morphosis) has facilitated the shift from a rather one-directional information deficit model in science communication to a more bidirectional communication corresponding to a dialogue model. Little is known about the preferences for social media communication from the supply side of institutional and scholarly communication. Analyzing survey data from nearly 8,700 scientists, we compared their preferences for press media and social media, proxies of traditional centralized communication channels and modern decentralized channels, respectively. Our empirical results show that trust in governments and prioritizing access to all perspectives on the crisis are important factors that influence scientists’ preferences regarding forms of communication. Trust favors centralized systems, while social media serves as an alternative in contexts lacking trust in politics. Prioritizing the diffusion of different perspectives drives a shift to stated preferences for decentralized communication systems. We also show that scientists’ stated preferences for communication systems depend on the socio-political context.